Midwife-led birthing centre in the humanitarian setup: An experience from the Rohingya camp, Bangladesh. - Abdul Halim; Abu Sayeed Md Abdullah; Fazlur Rahman; Oliva Bazirete; Sabera Turkmani; Kirsty Hughes; Sofia Castro Lopes; Andrea Nove; Mandy Forrester; Vanessa Scarf; Emily Callander; Caroline S E Homer (PLOS Global Public Health)
In Bangladesh, Midwife Led Birthing Centres (MLBCs) have been established to provide midwifery care and sexual and reproductive health services for the displaced Rohingya population in Cox's Bazar. The aim of this study was to explore MLBCs in this humanitarian context from the perspectives of women, midwives, and other key stakeholders. A mixed-method case study was conducted at one of the MLBCs within the Rohingya refugee camps in Cox's Bazar. The MLBC serves a population of approximately 8,500 people. Quantitative data were collected from the medical records and documents of the MLBC. Qualitative data included two key informant interviews (KIIs) with policy makers, one focus group discussion (FGD) with 7 midwives and ten in-depth interviews (IDIs) with Rohingya women who gave birth in this MLBC. Thematic analysis of qualitative data was performed. In 2022, 267 women gave birth at the MLBC, and 70 women with complications were transferred to higher-level facilities. Women chose the MLBC because of the respectful care provided by kind and skillful midwives, and the high-quality services. The MLBC was often recommended by community volunteers and relatives. Midwives provided a range of health services including antenatal, labour and birth, postnatal, family planning, mental health support and gender-based violence services. Challenges included language barriers, difficulty obtaining transport from home and back particularly at night in remote areas, security fears and weak cell phone coverage that affected communication for referral and follow-up. Recommendations included increased support and security staff, establishing a referral hospital nearer to the camp, refresher training for midwives and monitoring, and mentoring to improve service quality. The MLBC in the Rohingya camp shows that respectful midwifery care including management and referral of obstetric complications with wider sexual and reproductive health services can be provided in a humanitarian setting to optimize maternal and neonatal health outcomes.